Electro–Thermal 1D model of the SIS100 superconducting dipole magnet. (September 2020) - Szwangruber, P.; Raginel, V.; Freisleben, W.; Roux, C.
Highlights: FDM implicit scheme (unconditionally stable) used for thermal calculation. Quench in SC coils with strong thermal anisotropy can be modelled in 1D. Voltage nodal analysis enables calculation of inter-turn voltages. Abstract: The FAIR Project – a new international Facility for Antiproton and Ion Research is under construction in Darmstadt, Germany. The core machine at FAIR is the SIS100 synchrotron which utilises superconducting magnets in order to guide the heavy ion beam. The bending component of the magnetic field is generated by super-ferric window-frame dipole magnets symmetrically distributed over the six arc sections of the accelerator ring. The dipole coils are wound with a LTS low AC loss Nuclotron-type cable. Due to the very thick inter-turn insulation, the coil is characterized by a strong anisotropy of thermal conductivity which enables application of a 1D electro-thermal model. This work presents the latest version of the magnet model used for the simulation of magnet's operating modes at the test facility (including quench). Since currently the series dipole magnets undergo acceptance tests at cryogenic conditions, the simulation results are compared to the available measurements.